Applying Heterarchy Theory to Ancient Mesopotamian Religions: A View from Assur - Zaia, Shana (Numen, 2023)
Heterarchy theory is a valuable tool for analyzing complex and changing relationships between elements in a system. It has been employed in anthropology, archaeology, and recently in religious studies. Its utility has not yet been exploited for religions that are studied through textual evidence, such as Mesopotamian religions. As Mesopotamian religions were polytheistic and the texts represent multiple genres from a broad timeframe, relationships between system actors such as gods, temples, and cities defy static and lineal arrangements. Heterarchies are well suited for untangling these relationships, showing how they change depending on the measuring criteria. Using the case of the city of Assur, which housed many deities and was both the religious center and a political capital, heterarchy theory shows how the same elements – temples and cities – reveal different rankings that coexisted simultaneously. Heterarchies productively complicate our understanding of these religious relationships and expose the multimodality of each element in the system.